Opportunities for a national genomic data governance framework in Australia: a systematic review - Fabian Cannizzo; Miranda E. Vidgen; Rebekah McWhirter; Alan Petersen; Margaret Otlowski; Marco Rizzi; Jasmine Hensley; Ainsley J. Newson (BMC Medical Ethics)
Abstract Background As with other countries, Australia is seeking to make efficient use of genomic data for use in research, clinical medicine and population health. However, to enable cross jurisdictional consistency in the management of and access to data, it will first need to establish a national framework for governing genomic data. To this end, ethical, legal and social issues are often discussed. However, the literature offers little evidence-based support for such a framework. Methods To address this literature gap, we systematically reviewed two databases (Scopus and PubMed) for research articles that discussed issues and opportunities for enacting genomic data governance frameworks in the domains of research, genomic medicine and public (population) health in the Australian context. Results Thirty-one relevant articles were included and were analysed using inductive content analysis. Our findings identified that opportunities for implementing a national genomic data governance framework concerned defining roles for patients in data governance, data management processes and increasing the public acceptance of genomic data use in healthcare and research. Additionally, they highlight differences in the opportunities and priorities for clinical and research genomics that hinder further advancement of data governance. Conclusions Our synthesis of the current literature on genomic data governance suggests that the current focus on individual consent as the primary mechanism for protecting data subjects and different priorities in clinical and research governance need to be addressed. Given the significance of the role of consent procedures and differences in clinical and research data in generating a data governance framework, our findings hence reveal a critical gap in the research literature. Advancing a national genomic data governance framework will require greater consensus and clarity regarding the application of ethical principles across jurisdictions and institutions.